2002
DOI: 10.1159/000064322
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Non-Hodgkin’s Lymphoma – a Difficult Differential Diagnosis

Abstract: Introduction: Primary renal lymphoma (PRL) as a clinical entity is not undisputed because the kidneys do not contain lymphatic tissue and the mechanism of development of PRLs is unclear. Most of the few cases reported showed rapid systemic progression and a poor prognosis. Although there are no clearly defined diagnostic criteria for renal lymphomas, abdominal and thoracic computed tomography as well as renal and bone marrow biopsy are recommended. 3 cases of renal lymphoma are reported and their diagnosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Acute kidney injury as a presenting symptom of lymphomatous infiltration of kidney parenchyma was reported earlier [21][22][23]. The proposed mechanisms of such clinical presentation included tubular compression and impairment of renal parenchymal blood flow and increased vascular resistance [23,24]. In our series, acute kidney injury was not associated with any specific type of glomerular injury, but was more commonly seen in cases with massive interstitial involvement associated with destruction of the normal renal architecture, similar to the previously reported cases.…”
Section: Discussionsupporting
confidence: 87%
“…Acute kidney injury as a presenting symptom of lymphomatous infiltration of kidney parenchyma was reported earlier [21][22][23]. The proposed mechanisms of such clinical presentation included tubular compression and impairment of renal parenchymal blood flow and increased vascular resistance [23,24]. In our series, acute kidney injury was not associated with any specific type of glomerular injury, but was more commonly seen in cases with massive interstitial involvement associated with destruction of the normal renal architecture, similar to the previously reported cases.…”
Section: Discussionsupporting
confidence: 87%
“…Pathophysiological characteristics of AKI in patients with renal involvement by non-Hodgkin lymphoma are believed to be tubular compression and impairment of renal parenchymal blood flow [2], which might have occurred from the massive lymphocytic infiltration and severe interstitial edema noted in our patient. The rapid improvement in renal function that our patient experienced after chemotherapy suggests that lymphomatous infiltration was the sole cause of her renal dysfunction.…”
Section: Discussionmentioning
confidence: 72%
“…Renal involvement can be either primary renal lymphoma (PRL) or associated with extrarenal non-Hodgkin lymphoma. PRL as a clinical entity has been disputed because the kidneys do not contain lymphoid tissue, and the mechanism of development of PRL is unclear [2]. The diagnosis of PRL should be made only in the absence of extrarenal lymphoma, paraproteinemia, and leukemic blood phase [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that PRL originates from the renal capsule and infiltrates the renal parenchyma. Another explanation is that chronic inflammatory conditions of the kidney attract the infiltration of lymphoid cells and eventually evolve into lymphoma (5).…”
Section: Introductionmentioning
confidence: 99%